HUBUNGAN PERILAKU KONSUMSI MIE INSTAN DENGAN TINGKAT INDEKS MASSA TUBUH (IMT) PADA WARGA DI RT 03 DESA BUNIAYU KABUPATEN TANGERANG - Imelda Agustin; Zahra Maulidi Septimar; Siti Rochmani; Ida Farida (Nusantara Hasana Journal, 2022)
Changes in eating habits can be caused by factors of education and health as well as food marketing or distribution activities. The consumption of instant noodles in Indonesia is high. Body mass index (BMI) is an easy and simple method for assessing nutritional status in an individual, but it cannot measure body fat directly. The aims of the research to determine the relationship between instant noodle consumption behavior and Body Mass Index in Rt 03 Buniayu Residents, Tangerang Regency. This study used a correlation descriptive design. this refers to quantitative research. This study used a crosssectional approach. Based on the results of research conducted at household 03 Buniayu Village, Tangerang Regency, 2020 with a total of 60 respondents. Based on the chi-square test that the p-value is 0.158> 0.05, it can be stated that there is no relationship between instant noodle consumption behavior and body mass index in Rt 03 Buniayu Village, Tangerang Regency 2020.